Evaluation of 30 MPa Concrete Strength Using Inferential Statistics and Control Charts - Noor Ainun Cholis; Eswan Eswan; Wahyu Mahendra (Institut Teknologi Adhi Tama Surabaya, 2026)
This study aims to evaluate the quality and statistical control of 30 MPa concrete used in the construction of the Main Genset Building at Nusantara Capital City (IKN). The primary objective is to determine whether the concrete meets the design specifications and assess the statistical capability of its production process. A total of 69 concrete cylinder samples tested at 28 days were analyzed using two quantitative approaches: inferential statistics (normality test and one-sample t-test) and statistical quality control tools (control charts and process capability analysis).Descriptive statistical analysis revealed that the average compressive strength at 28 days reached 33.464 MPa, exceeding the target value of 30 MPa. The normality test confirmed a normal distribution, validating the use of the T-test, which showed a statistically significant and positive deviation from the design strength. Control chart analysis indicated that the production process was stable and statistically controlled, fulfilling the prerequisites for process capability evaluation.The process capability index (Cpk) was calculated at 1.101, suggesting that the production process is capable of meeting specification limits. However, the slightly lower Cpk compared to Cp (1.193) indicates a shift in the mean compressive strength toward the upper specification limit. The study concludes that the concrete quality meets design requirements with satisfactory process control, but recommends tighter control of material variability and adjustment of production settings to center the strength distribution, enhancing efficiency and reducing future quality risks.